EXPLORING THE RELATIONSHIP BETWEEN PSYCHOLOGICAL CONTRACT BREACH AND EMPLOYEE VOICE IN THE HOTEL INDUSTRY: AN EMPIRICAL STUDY - Sheikh Sajid Mohammad,Nazir A Nazir (EPRA International Journal of Economic and Business Review(JEBR), 2023)
This study aims to investigate the role of psychological contract breach as a predictor of employee voice behavior. For this study, data was collected from employees working in “A” category hotels in Srinagar, Kashmir, India. The findings offer empirical evidence supporting the hypothesis that psychological contract breach (PCB) has a negative relationship with employee voice (EV). The finding is consistent with social exchange theory, suggesting that employees' reactions are influenced by the treatment they receive from their organizations. The study contributes to the current body of literature on psychological contract breach and its impact on discretionary work behaviors.